Forecasting Cost Volume Profit dalam Pencapaian Penjualan pada Perum BULOG Periode 2019-2023 - Afifa Aini Gezanti; Nur Imam Taufik; Abdul Rahman; Iwan Kurniawan (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Profit planning is an essential component of financial management for state-owned enterprises such as Perum BULOG, which has a strategic role in maintaining national food security and ensuring sustainable financial performance. In this context, the present study aims to analyze the minimum sales volume required by Perum BULOG to avoid losses using Cost-Volume-Profit (CVP) analysis and to develop a combined model that integrates CVP with sales forecasting through the parabola method. This combined approach is expected to provide a more comprehensive foundation for profit planning and strategic decision-making. The research employs a descriptive quantitative approach using secondary data derived from Perum BULOG’s audited financial reports for the 2019–2023 period. CVP analysis includes the computation of Contribution Margin, Break-Even Point (BEP), Margin of Safety (MoS), and Degree of Operating Leverage (DOL), which together illustrate the company’s cost structure and sensitivity to sales fluctuations. Furthermore, sales forecasting with the parabola method is applied to capture historical fluctuation patterns more accurately than linear projections, thereby generating realistic sales targets for future periods. The findings indicate that Perum BULOG consistently achieved sales well above the break-even threshold, with the lowest BEP recorded at IDR 17.68 trillion in 2021 and the highest at IDR 30.36 trillion in 2023. The Margin of Safety rose significantly from 8.65% in 2019 to 34.08% in 2023, reflecting improved resilience against sales downturns. Meanwhile, variations in DOL highlight the degree to which operating profit is sensitive to sales changes. Parabola-based forecasting projects substantial sales growth, reaching IDR 64.71 trillion in 2024 and increasing further to IDR 126.35 trillion in 2026.